Pelatihan Kepemimpinan Komti Sebagai Role Model Pada Mahasiswa Pendidikan Ekonomi Universitas Palangka Raya - Putri, Windy Utami; Hariatama, Fendy; Oktobery, Revnussa; Lenlioni, Liling; Buji, Grace Evelina (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
Economic Education students are expected to have strong leadership skills to become competent educators and professionals. One of the activities closely related to leadership among students is serving as a class commander. However, based on initial observations, many students still lack experience and knowledge in leadership, particularly in serving as a class commander. Some students holding this position still struggle to manage their peers and do not yet understand how to be an effective role model for those around them. The purpose of this community service initiative is to shape students into role models who understand professionalism and leadership ethics. The method used is training on "Class Commander Leadership as a Role Model." The community service activity, conducted through face-to-face training, ran smoothly and successfully. The activity involved discussions on topics related to class commander leadership as a role model. Overall, the training for students to gain new insights was deemed successful, as evidenced by the participants' satisfaction after attending the program.